1985
DOI: 10.1002/app.1985.070301005
|View full text |Cite
|
Sign up to set email alerts
|

The turbulent drag reduction by graft copolymers of guargum and polyacrylamide

Abstract: SynopsisCommercial guargum is known to be a shear stable drag reducing agent. However, the aqueous solutions of guargum start degrading within 8 hrs. of their preparation and after 65 hrs., they degrade completely. In the present investigation, the graft copolymers of guargum and polyacrylamide have been prepared. It has been shown that the purification and grafting enhance the drag reduction effectiveness and biodegradation resistance considerably in guargum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 6 publications
1
35
0
Order By: Relevance
“…It has been found that grafted copolymer shows better performance than LBG itself. The major mechanism of flocculation by polymers is bridging [21] . The bridging takes place by adsorption of a polymer molecule at more than one site on a particle or at sites on different particles.…”
Section: Flocculation Studymentioning
confidence: 99%
“…It has been found that grafted copolymer shows better performance than LBG itself. The major mechanism of flocculation by polymers is bridging [21] . The bridging takes place by adsorption of a polymer molecule at more than one site on a particle or at sites on different particles.…”
Section: Flocculation Studymentioning
confidence: 99%
“…They found that the grafted GG copolymer combined the robustness of GG and the efficiency of the synthetic PAAM polymer, resulting in enhanced drag reduction efficiency. Moreover, Deshmukh et al [86] studied the grafting of polyacrylamide onto GG, and compared the graft polymer with commercial GG and purified GG. They found that the grafted GG and purified GG exhibited good biodegradation resistance and enhanced drag reduction efficiencies.…”
Section: Guar Gummentioning
confidence: 99%
“…It has been found that graft copolymer (GG-g-AGA) shows better performance (lesser turbidity over lowest polymer dose) than guar gum. This could be explained due to the fact that in graft copolymer, the dangling longer poly-PAGA chains have better approachability to the contaminant [28][29].…”
Section: Flocculation Studymentioning
confidence: 99%